Effect of mulch and plant distribution in the field on some growth and development parameters of sorghum - Wendt, Wilmar (Pesquisa Agropecuaria Brasileira, 2014)
With the purpose of verifying, by the growth analysis method, the response of grain sorghum crop (Sorghum bicolor (L.) Moench) to the variations of some environmental factors introduced by the use of dead mulching at different plant population rates, a trial was established at the experimental field of the Physics and Meteorology Department of Escola Superior de Agricultura Luiz de Queiroz. Data on soil temperature were obtained at 2, 5, 10 and 20 cm depths for each treatment. From the analysis of the results obtained in this work, a variation in the behavior of sorghum crop was observed as a consequence of the effects caused by dead mulching. Based on the physiological parameters evaluated, one can conclude that the effect of dead mulching, processed through the soil temperature regime, was higher than the effect resulting from the spacing used.